Does skeletal muscle carnitine availability influence fuel selection during exercise? - Stephens, Francis B. (Proceedings of the Nutrition Society, 2018)
Fat and carbohydrate are the major fuel sources utilised for oxidative, mitochondrial ATP resynthesis during human skeletal muscle contraction. The relative contribution of these two substrates to ATP resynthesis and total energy expenditure during exercise can vary substantially, and is predominantly determined by fuel availability and exercise intensity and duration. For example, the increased ATP demand that occurs with an increase in exercise intensity is met by increases in both fat and carbohydrate oxidation up to an intensity of approximately 60–70 % of maximal oxygen consumption. When exercise intensity increases beyond this workload, skeletal muscle carbohydrate utilisation is accelerated, which results in a reduction and inhibition of the relative and absolute contribution of fat oxidation to total energy expenditure. However, the precise mechanisms regulating muscle fuel selection and underpinning the decline in fat oxidation remain unclear. This brief review will primarily address the theory that a carbohydrate flux-mediated reduction in the availability of muscle carnitine to the mitochondrial enzyme carnitine palmitoyltransferase 1, a rate-limiting step in mitochondrial fat translocation, is a key mechanism for the decline in fat oxidation during high-intensity exercise. This is discussed in relation to recent work in this area investigating fuel metabolism at various exercise intensities and taking advantage of the discovery that skeletal muscle carnitine content can be nutritionally increased in vivo in human subjects.